2022
DOI: 10.3390/ijerph19031259
|View full text |Cite
|
Sign up to set email alerts
|

In the Labyrinth of Dietary Patterns and Well-Being—When Eating Healthy Is Not Enough to Be Well

Abstract: This paper aims to identify the relation between food consumption and well-being, and the level of well-being depending on a diet followed. Moreover, we analyze whether people driven by single motives, such as the health, pleasure or social dimension of food declare the lower or higher level of well-being than those motivated by a larger number of factors. The survey was conducted online (CAWI, n = 1067). The following scales were used: Satisfaction With Life Scale (SWLS), Satisfaction with Food-related Life S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 64 publications
(97 reference statements)
2
9
2
Order By: Relevance
“…Moreover, the differences found in some of the items of the FQSE showed that the three profiles had adequate and inadequate eating habits. These results contradict previous findings linking healthier diets to higher levels of life ( 6 , 7 , 11 , 28 , 37 , 45 ) and food-related life satisfaction ( 2 , 7 , 13 , 14 , 17 , 19 ) in older adults. However, satisfaction with food-related life not only encompasses nutritional issues but also the social dimension of food, pleasure, and positive emotions ( 7 , 71 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, the differences found in some of the items of the FQSE showed that the three profiles had adequate and inadequate eating habits. These results contradict previous findings linking healthier diets to higher levels of life ( 6 , 7 , 11 , 28 , 37 , 45 ) and food-related life satisfaction ( 2 , 7 , 13 , 14 , 17 , 19 ) in older adults. However, satisfaction with food-related life not only encompasses nutritional issues but also the social dimension of food, pleasure, and positive emotions ( 7 , 71 ).…”
Section: Discussioncontrasting
confidence: 99%
“…A better perceived economic situation was also linked to food-related life satisfaction in these profiles, in line with previous findings ( 14 16 ). However, our results suggest that this positive association does not relate to access to healthier diets ( 7 , 14 , 46 ) but to the hedonic and social dimension of food ( 2 , 17 , 45 ). Overall, these results show that financial wellbeing and distress are related to degrees of vulnerability in older adults.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…For the variable AHEI, the scores obtained for each of the members of the families were different in the four profiles: mothers and adolescents in Profile 3 presented the highest average AHEI scores as well as the highest levels of SWFoL. This is in line with the quality of the diet being directly related to SWFoL in adults and adolescents [ 59 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 84%